THE SOCIAL INTERACTION OF BLACK AND WHITE AMERICANS IN "FILM THE HATE U GIVE” - Mahmud, Muhlys; Sunra, La; Abdullah, Abdullah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
Social interaction is something we usually do and carry out every day. Social interaction can be interpreted as a dynamic social relationship. The social relationship in question can be a relationship between individuals and other individuals, between groups and other groups, or between groups and individuals. This social interaction is used by individuals or groups to build relationships, help solve problems and even cause chaos. Social interaction in literary works is intended to create and group interactions using Robert Alexandra Nisbet's theory to make it easier for readers. One of them is social interaction contained in the analysis of The Social Interaction Of Black And White Americans In The Film The Hate U Give. This research aims to determine the types of social interactions in the film The Hate U Give by Angie Thomas. This research uses a descriptive method according to Robert A. Nisbet's theory. This data was taken from the film The Hate U Give by Angie Thomas. This film tells the story of a black girl named Starr Carter. Data was analysed by watching the film many times as possible. I want to understand all interactions and conversations. The writer categorizes several interactions in the film that show the types of social interaction in the film The Hate U Give, and what is the meaning of social interaction based on context played by the main character and other characters. themes and depictions of social interactions used by the author Angie Thomas. The research results show that the types of social interaction in the film The Hate U Give by Angie Thomas include: exchange, cooperation, competition, conformity, coercion and conflict. and also, Angie Thomas's role is very influential in creating social interactions where the atmosphere of the event can be directly felt. And the conclusion of this research is that in the film The Hate U Give by Angie Thomas which tells the story of a black girl named Starr Carter. Starr lives between two different environments.Keywords: Social Interaction, Types of Social Interaction, The Hate U Give